Role of the SH3-Ligand Domain of Simian Immunodeficiency Virus Nef in Interaction with Nef-Associated Kinase and Simian AIDS in Rhesus Macaques - Khan, Imran H. (American Society for Microbiology, 1998)
The nef gene of the human and simian immunodeficiency viruses (HIV and SIV) is dispensable for viral replication in T-cell lines; however, it is essential for high virus loads and progression to simian AIDS (SAIDS) in SIV-infected adult rhesus macaques. Nef proteins from HIV type 1 (HIV-1), HIV-2, and SIV contain a proline-Xaa-Xaa-proline (PxxP) motif. The region of Nef with this motif is similar to the Src homology region 3 (SH3) ligand domain found in many cell signaling proteins. In virus-infected lymphoid cells, Nef interacts with a cellular serine/threonine kinase, designated Nef-associated kinase (NAK). In this study, analysis of viral clones containing point mutations in the nef gene of the pathogenic clone SIVmac239 revealed that several strictly conserved residues in the PxxP region were essential for Nef-NAK interaction. The results of this analysis of Nef mutations in in vitro kinase assays indicated that the PxxP region in SIV Nef was strikingly similar to the consensus sequence for SH3 ligand domains possessing the minus orientation. To test the significance of the PxxP motif of Nef for viral pathogenesis, each proline was mutated to an alanine to produce the viral clone SIVmac239-P(104)A/P(107)A. This clone, expressing Nef that does not associate with NAK, was inoculated into seven juvenile rhesus macaques. In vitro kinase assays were performed on virus recovered from each animal; the ability of Nef to associate with NAK was restored in five of these animals as early as 8 weeks after infection. Analysis of nef genes from these viruses revealed patterns of genotypic reversion in the mutated PxxP motif. These revertant genotypes, which included a second-site suppressor mutation, restored the ability of Nef to interact with NAK. Additionally, the proportion of revertant viruses increased progressively during the course of infection in these animals, and two of these animals developed fatal SAIDS. Taken together, these results demonstrated that in vivo selection for the ability of SIV Nef to associate with NAK was correlated with the induction of SAIDS. Accordingly, these studies implicate a role for the conserved SH3 ligand domain for Nef function in virally induced immunodeficiency.